Adolescent PR3-ANCA-positive hypertrophic pachymeningitis: A case report and review of the literature. Issue 17 (April 2018) - Matsumoto, Kotaro; Akiyama, Mitsuhiro; Kajio, Nobuhiko; Otomo, Kotaro; Suzuki, Kazuko; Nishina, Naoshi; Kasuya, Kento; Oishi, Naoki; Kameyama, Kaori; Takeuchi, Tsutomu
Abstract: Rationale: Hypertrophic pachymeningitis (HP) is an uncommon, life-threatening disease that is seen in elderly patients with antineutrophil cytoplasmic antibody (ANCA) positivity. Proteinase-3 (PR3)-ANCA-positive HP has not been reported in adolescents. Here, we report the first case of adolescent PR3-ANCA-positive HP successfully treated with immunosuppressive therapy. Patient concerns: A 14-year-old female presented with fullness and pain in her right ear unresponsive to antibiotics. Laboratory tests showed an elevated C-reactive protein and PR3-ANCA positivity. Computed tomography and magnetic resonance imaging revealed mastoiditis in the right temporal bone. Surgical biopsy revealed severe fibrosis and prominent inflammatory-cell infiltration. She received prednisolone and methotrexate therapy, and then underwent a right mastoidectomy. Five months later, she developed headache, dysarthria, and multiple cranial nerve palsies. Further imaging revealed enhancement and thickening of the right hemispheric dura. Diagnosis: PR3-ANCA-positive HP. Interventions: She was successfully treated with steroid pulse therapy for 3 days, followed by high doses of prednisolone and intravenous cyclophosphamide. Outcome: The treatment resulted in significant improvement of her symptoms, laboratory data, and radiologic findings. Lessons: PR3-ANCA-positive HP can present not only in the elderly, but also in adolescence, and prompt diagnosis and treatment with immunosuppressive therapy is vital.